-
-x square y + 8xy - 15y = -x (x-3) (x-5) x to the 2n power - 5x to the n power - 66 = (x n + 6) (x n - 11) 3 to the 2m power + 3 m + 2 to the power + 81 quarters = (3 m + a m + 2 power + 3a square x - 2a m power y-6xy = (a 2-2y) (a m + 3a 2 x).
x to the 2n power + 6x to the n power - y squared + 9 = (x n + y + 3) (x n - y + 3).
x squared + x) squared - 14 (x square + x) + 24 (to process) The square of x + x is regarded as a term t, and the original formula = (t-2) (t-12) == (x 2 + x-2) (x 2 + x-12).
ab+ac—b squared—2bc—c squared (process) (ab+ac)-(b2+bc)-(bc+c2)a(b+c)-b(b+c)-c(b+c).
a-b-c)(b+c)
x—y) squared—4(x-y+15) process.
Think of x-y as t, and the original formula = t 2-4t-60
Use cross multiplication = (t+6)(t-10).
x-y+6)(x-y-10)
ax+ay+bx+by—a—b process.
a(x+y)+b(x+y)-(a+b)
a+b)(x+y)-(a+b)
a+b)(x+y-1)
Ten x square (x square + y squared) — 20y four times.
Cross multiplication, -20y quadratic to -4y 2*5y 2 original = (x 2-4y 2) (x 2 + 5y 2) (x-2y) (x + 2y) (x 2 + 5y 2).
-
1 -y(x-3)(x-5)
2 (x to the nth power - 11) (x to the nth power +6) 3 (3 to the m power + 9/2).
4 (a to the m power + 3x) (a -2y).
5 (x+3-y)(x+3+y)
6 (x²+x)²-14(x²+x)+24((x²+x)-2)((x²+x)-12)(x+2)(x-1)(x+4)(x-3)
7 ab+ac-b²-2bc-c²
a(b+c)-(b+c)²
a-b-c)(b+c)
8 (x-y)²-4(x-y+15)
x-y)²-4(x-y)-4*3*5
x-y)-2*5)((x-y)+2*3)(x-y-10)(x-y+6)
9 ax+ay+bx+by-a-b
a(x+y)+b(x+y)-(a+b)
a+b)(x+y)-(a+b)
a+b)(x+y-1)
10 x²(x²+y²)-20(y²)²
x²) x²y²-20(y²)²
x²+5y²)(x²-4y²)
x²+5y²)(x-2y)(x+2y)
-
y(x-3)(-x+5)
x^n-11)(x^n+6)
3^m + 9/2)^2
I didn't get it. x^n+3-y)(x^n+3+y)
x^2+x)^2-14(x^2+x)+24 = (x^2+x)^2-(2+12)(x^2+x)+(2*12)=(x^2+x-2)(x^2+x-12)=(x+2)(x-1)(x+4)(x-3)
ab+ac-b^2-2bc-c^2 = a(b+c) -b+c)^2 = (a-b-c)(b+c)
x-y)^2 - 4(x-y+15) = (x-y)^2-4(x-y)-60 = (x-y)^2-(10-6)(x-y)-6*10 = (x-y-10)(x-y+6)
ax+ay+bx+by-a-b = a(x+y-1) +b(x+y-1) = (a+b)(x+y-1)
What's the last line?
-
2x^2+4xy=2x(x+2y)
4x^2-12xy=2*2x(x-3y)
The common factor of the polynomial 2x 2+4xy and 4x 2-12xy is 2x
-
One. 1. Sum difference (a+b)(a-b)=a 2+b 2 (2 is the meaning of 2 squared) polynomial. Two. 1、c
2. D is definitely right.
-
The product of the sum of the two numbers and the difference between the two numbers is equal to the square difference of the two numbers and the formula is.
a+b)(a-b)=a-b, polynomial.
ii 1c 2d
-
1.Compute.
Original = (Original = (2010-1) (2008+1) - 2008 2010
Original = (100-1) (100+1) (10000+1).
2.Knowing that x -y = 6 and x + y = 3, find the value of x-y.
Solution: x -y = (x + y) (x-y) = 3 (x-y) = 6
x-y = 2 two. Observe the following types and explore the patterns:
Use the equation with a positive integer n to express the law you have found:
n(2n+1)=(2n)2-1
Three. Multiple choice questions.
1.(x-y-3) +x-y+5) =0, then the value of x -y =0 is ( ).
b.-8 d.-15
Solution: (x-y)2-6(x-y)+9+(x-y)2+25+10(x-y)=2(x-y)2+4(x-y)+36=0
x-y)2+2(x-y)+18=0
There is a problem with this question, please check the question carefully!
Four. Fill-in-the-blank questions.
1.If x+y=-1 and x-y=-3, then x-y = 3
2.If the result of the calculation (a+m) (a+1 2) does not contain a primary term for the letter a, then m= is equal to -1 2
3.When x=3 and y=1, the value of the algebraic equation (x+y)(x-y)+y is 9
Five. Answer the questions.
1.Try to show that the square difference of two adjacent positive integers is odd.
Solution: (k+1)2-k2=k2+1+2k-k2=2k+1
is an odd number of 2Calculation: (2+1) (2 +1) (2 4+1) ....2^2n+1)
2-1)(2+1)×(2²+1)×(2^4+1)×…2^2n+1)=2^(2n+1)-1
-
1.(1) Original = (60+
2) Original formula = 2009 * 2009-2008 * 2010 + 2009-2009 = 2009 * 2010-2008 * 2010-2009 = 1
3) Original formula = (100 + 1) * (100-1) * 10001 = (10000-1) * (10000 + 1) = 100000000-1 = 99999999
2 n*(n+2)=(n+1)squared-1 multiple-choice.
1.Can't read it, the title is correct?
Fill-in-the-blank question 1Equal to 3
2.Minus 1 2
3.Equal to 9
Five. 1.(n+1) -n =2n+1 is the odd number 2Original = (2-1) (2+1) (2 +1) (2 4+1) ....2^2n+1)
2²-1)×(2²+1)×(2^4+1)×…2^2n+1)=(2^4-1)×(2^4+1)×…2^2n+1)=(2^2n -1)×(2^2n +1)
2^4n -1
-
One. 1.(1) Original = (
2) Original formula = 2009 - (2009-1) (2009 + 1) = 2009 - 2009 + 1 = 1
3) Original formula = (100-1) (100 + 1) 10001 = 9999 10001 = (10000-1) (10000 + 1) = 10000 -1
6=3(x-y)
x-y = 2 two. (2n-1)(2n+1)=(2n)-1iii. 1.That's a bit of a problem!!
Four. 1. 3
Five. 1.(n+1) -n =2n+1 is the odd number 2Original = (2-1) (2+1) (2 +1) (2 4+1) ....2^2n+1)
2²-1)×(2²+1)×(2^4+1)×…2^2n+1)=(2^4-1)×(2^4+1)×…2^2n+1)=(2^2n -1)×(2^2n +1)
2^4n -1
-
Know the answer ... It's hard to put it into account.
Zeno tortoise. Achilles was a hero of ancient Greek mythology. In his race with the tortoise, he was ten times faster than the tortoise, the tortoise ran 100 meters in front and he chased behind, but he couldn't catch up with the tortoise. >>>More
1.Set the number of workers in the production of round and square respectively x, y, by the inscription. >>>More
a c b Above is the diagram of the first question.
Because ac+bc=ab, ac=1 2ab; >>>More
Like is changed to likes (third person singular), speaks is changed to speak (verb after modal verb is primitive), bored is changed to boring (bored is to describe people, boring is to describe things, many words are like this). >>>More